Linked Open Data Driven Game Generation - Warren, R.; Champion, Erik (Springer International Publishing., 2014)
Linked Open Data provides a means of unified access to large and complex interconnected data sets that concern themselves with a surprising breath and depth of topics. This unified access in turn allows for the consumption of this data for modelling cultural heritage sites, historical events or creating serious games. In the following paper we present our work on simulating the terrain of a Great War battle using data from multiple Linked Open Data projects.